ECHOES OF CONFORMITY: A BIBLIOMETRIC ANALYSIS OF INSTITUTIONAL ISOMORPHISM IN PUBLIC SECTOR STUDIES - Mohd Nadzari, Nor Ashikin; Yussof, Salwa Hana; Isa, Khadijah; Zakaria, Zamzulaila (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The concept of institutional isomorphism, first introduced by DiMaggio and Powell, has increasingly shaped understandings of how public sector organisations respond to external pressures, including regulatory mandates, professional norms, and environmental uncertainty. However, previous literature often overlooks the complex interplay between these pressures across governance levels and varied contexts. To address this gap, this study employs bibliometric tools, including Scopus Analyzer, OpenRefine, and VOSviewer, to systematically analyze 304 documents published between 1992 and 2025. The analysis maps publication trends, co-authorship networks, influential authors, and keyword co-occurrences, providing a nuanced picture of research patterns and thematic developments. Key findings reveal a marked growth in publications since 2010, peaking around 2020–2022, with contributions from a diverse range of countries and interdisciplinary collaborations. The co-authorship network highlights the central roles of authors such as Powell W.W. and Oliver C., while emerging scholars and regions, including Malaysia and China, reflect a widening global interest in the field. Keyword analysis further identifies evolving research themes, from traditional concerns of legitimacy and compliance to contemporary emphases on sustainability, environmental management, and innovations. This study contributes to the literature by highlighting the extent and dynamics of scholarly engagement with institutional isomorphism in public sector contexts and the emerging directions for future research. The findings underscore the growing complexity and relevance of institutional theory in understanding public sector transformations in an increasingly interconnected and regulated world.